Spontaneous electromagnetic radiation in water areas: a new experiment and applications - V.N. Shuman; V. P. Kobolev; Yu. A. Bogdanov; I. G. Zakharov; D. A. Yatsyuta (Геофизический журнал, 2011)
New experimental data on registration of electromagnetic emission in radio-wave (kiloherts) range obtained on water areas of the Black Sea and the Sea-of-Azov have been given. The actual problem is being discussed on relation of theory and experiment during the studies of the processes of generation and distribution of seismo-acoustic-electromagnetic disturbances in lithosphere, their transformation in the system lithosphere- marine medium-atmosphere, their electromagnetic component removal to the day surface and into the atmosphere. The attention is concentrated on the physical mechanisms of seismic-acoustiv-hydro-electromagnetic transformations and informational possibilities of the method for the studies of the structure of geomedium and dynamic processes under the sea bottom.